PEMIKIRAN HADIS ‘ABDULLAH AL-HARARI Studi Kajian Ulama’ Hadis Modern-Kontemporer - Ianatussoleh; Masruroh (Al-Hasyimi: Jurnal Ilmu Hadis, 2024)
This study examines the hadith thought of Abdullah al-Harari, a scholar from Harar, Ethiopia, who made significant contributions to the study of hadith. The research adopts the library research method, focusing on four main aspects: the biography of Abdullah al-Harari, his educational background, the influence of his thoughts on hadith studies, and his ideas regarding hadith. The findings reveal that Abdullah al-Harari, born in the early 20th century and known as